Efficient Perovskite Hybrid Photovoltaics via Alcohol‐Vapor Annealing Treatment. (20th November 2015) - Liu, Chang; Wang, Kai; Yi, Chao; Shi, Xiaojun; Smith, Adam W.; Gong, Xiong; Heeger, Alan J.
Abstract : In this work, alcohol‐vapor solvent annealing treatment on CH3 NH3 PbI3 thin films is reported, aiming to improve the crystal growth and increase the grain size of the CH3 NH3 PbI3 crystal, thus boosting the performance of perovskite photovoltaics. By selectively controlling the CH3 NH3 I precursor, larger‐grain size, higher crystallinity, and pinhole‐free CH3 NH3 PbI3 thin films are realized, which result in enhanced charge carrier diffusion length, decreased charge carrier recombination, and suppressed dark currents. As a result, over 43% enhanced efficiency along with high reproducibility and eliminated photocurrent hysteresis behavior are observed from perovskite hybrid solar cells (pero‐HSCs) where the CH3 NH3 PbI3 thin films are treated by methanol vapor as compared with that of pristine pero‐HSCs where the CH3 NH3 PbI3 thin films are without any alcohol vapor treatment. In addition, the dramatically restrained dark currents and raised photocurrents give rise to over ten times enhanced detectivities for perovskite hybrid photodetectors, reaching over 10 13 cm Hz 1/2 W −1 (Jones) from 375 to 800 nm. These results demonstrate that the method provides a simple and facile way to boost the device performance of perovskite photovoltaics. Abstract : High performance of perovskite photovoltaics (perovskite solar cells and perovskite photodetectors) is realized by alcohol‐vapor solvent annealing treatment on CH3 NH3 PbI3 thin films to enhance the crystal growth and the grain size of the CH3 NH3 PbI3 crystals.